FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN METODE PERSEDIAAN (Studi Empiris Perusahaan Manufaktur di Bursa Efek Indonesia) - Ardiani Ika Sulistyawati; Iin Indri Lestari; Aprih Santoso (Politeknik Negeri Malang, 2020)
The reseach purpose is to analyze the selection of inventory accounting methods and the factors that influence decision making accounting methods to be used. The research examines four independent variables, namely the variability of inventory, companies size, current ratio and inventory turnover ratio. While the dependent variable in this study is the FIFO and average methods. The population of the research is 144 the manufacturing company listed on the Indonesia Stock Exchange in 2014-2017. The sample selection uses purposive sampling method, which is the determination of samples based on predetermined criteria. Then obtained a total sample of 48 companies during the period 2014-2017. This study uses a quantitative approach and the analysis technique uses is logistic regression, with SPSS version 22 analysis tools. The results of this research indicate that the variability of inventory and companies size does not significantly influence the selection of inventory acconting methods. While the current ratio and inventory turnover ratio significantly influence the selection of inventory acconting methods.